PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BOARD GAME “GUESS THE NUMBER” UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS - Rifda Nurafifah; Isna Rafianti; Nurul Anriani (LPPM Universitas Bina Bangsa, 2024)
The aim of this research is to produce a valid, practical, and effective learning media in the form of a board game to enhance students' critical thinking skills. The research uses the 4D model, consisting of the define, design, development, and disseminate stages. It was conducted in one of the middle school in Serang, involving seventh-grade students (one class). The result of this research and development is a learning board game named